2013
DOI: 10.1002/lary.24129
|View full text |Cite
|
Sign up to set email alerts
|

Level IIB lymph node metastasis in oropharyngeal squamous cell carcinoma

Abstract: This study uniquely demonstrated a statistically significant association between clinical tumor stage and tonsil subsite with level IIB metastasis in OPSCC. Considering the predicted incidence of nodal metastasis, we conclude that level IIB neck dissection can be omitted in early stage (T1 or T2) clinically node negative (cN0) OPSCC. In patients with a cN0 neck and advanced OPSCC (T3 or T4), primary tumor in the tonsil, or ipsilateral clinically node positive (cN(+) ) and contralateral cN0 neck, level IIB diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 37 publications
5
30
0
3
Order By: Relevance
“…The risk of metastases to cervical lymph nodes is high in oropharyngeal cancer, with an overall incidence of 92%, and an incidence of 39% for the clinically N0 neck, which suggests the need for elective treatment in the majority of the latter. However, the efficacy of elective neck treatment in clinically N0 oropharyngeal cancer has not yet been demonstrated with prospective studies, and observation is used as an option in some centers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk of metastases to cervical lymph nodes is high in oropharyngeal cancer, with an overall incidence of 92%, and an incidence of 39% for the clinically N0 neck, which suggests the need for elective treatment in the majority of the latter. However, the efficacy of elective neck treatment in clinically N0 oropharyngeal cancer has not yet been demonstrated with prospective studies, and observation is used as an option in some centers.…”
Section: Introductionmentioning
confidence: 99%
“…Gross et al found that the majority of the metastases were located in levels II and III. However, sublevel IIB metastases range between 2.5% and 6% in oropharyngeal cancers, suggesting that this sublevel can be omitted during elective neck dissection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total node counts for the entire neck specimen varied from 18 up to 119. Within level I, the range of node counts was also wide (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) with a mean number of nodes found in level I of 8.1. Node counts in the necks and node counts in the substations of level I are shown in Tables 3 and 4, respectively ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%